PERTUMBUHAN KREDIT AKIBAT TINGKAT INFLASI DAN SUKU BUNGA KREDIT DI INDONESIA - Nafaza Rahma; Rasyidin M. (Fakultas Ekonomi Universitas Almuslim Bireuen, 2023)
The research aims to examine the influence of inflation and credit interest rates on credit growth in Indonesia. This research uses quantitative methods, data analysis techniques using multiple linear regression models. From utilizing secondary data 2000-2022 from BPS. The results of this test show that inflation and credit interest rates have no effect on credit growth